POTENSI ZAKAT PERTANIAN PADI TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA TERUSAN DALAM KECAMATAN SUMBER MARGA TELANG KABUPATEN BANYUASIN - Yunica Adelia; Rudi Aryanto; Safitri Asrol (LPPM Universitas Nias Raya, 2026)
This study aims to analyzed the potential of rice agricultural zakat in improving community welfare and to examine the distribution mechanism of agricultural zakat in Terusan Dalam Village, Sumber Marga Telang District, Banyuasin Regency. The study employed a qualitative approach using field research. Data were collected through observations, in-depth interviews, and documentation involving rice farmers, mosque administrators, farmer group leaders, and community leaders. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the potential value of rice agricultural zakat in Terusan Dalam Village is estimated at approximately IDR 330,700,000 per harvest season, provided that all farmers whose harvests have reached the nisab fulfill their zakat obligations in accordance with Islamic law. However, the management of agricultural zakat has not yet been optimized, as its distribution is predominantly carried out directly to the poor, needy, relatives, neighbors, and other local community members without the involvement of an official zakat management institution. Consequently, the considerable potential of agricultural zakat has not been fully utilized as an instrument for community economic empowerment. Therefore, improving public literacy on agricultural zakat and strengthening the role of the National Board of Zakat (BAZNAS) are essential to ensure that zakat management becomes more effective, targeted, transparent, and sustainable in supporting community welfare.